2019
DOI: 10.1021/acs.jmedchem.8b01305
|View full text |Cite
|
Sign up to set email alerts
|

Design of Novel Inhibitors of Human Thymidine Phosphorylase: Synthesis, Enzyme Inhibition, in Vitro Toxicity, and Impact on Human Glioblastoma Cancer

Abstract: Overexpressed human thymidine phosphorylase (hTP) has been associated with cancer aggressiveness and poor prognosis by triggering proangiogenic and antiapoptotic signaling. Designed as transition-state analogues by mimicking the oxacarbenium ion, novel pyrimidine-2,4-diones were synthesized and evaluated as inhibitors of hTP activity. The most potent compound (8g) inhibited hTP in the submicromolar range with a noncompetitive inhibition mode with both thymidine and inorganic phosphate substrates. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 77 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…Other analogous TP inhibitors have also displayed no effect on the cell viability of U87 cells. 46 A concerning observation was that the nitroimidazolyl prodrugs 4 and 5 had more of an effect on cell viability than their corresponding active TP inhibitors in HAs (Figure S4B,C). Cytotoxicity was observed at high concentrations of the nitroimidazolyl prodrugs, but this is an undesirable property particularly in normal tissue, as the prodrug should have an inert cytotoxic profile.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other analogous TP inhibitors have also displayed no effect on the cell viability of U87 cells. 46 A concerning observation was that the nitroimidazolyl prodrugs 4 and 5 had more of an effect on cell viability than their corresponding active TP inhibitors in HAs (Figure S4B,C). Cytotoxicity was observed at high concentrations of the nitroimidazolyl prodrugs, but this is an undesirable property particularly in normal tissue, as the prodrug should have an inert cytotoxic profile.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Although the effect of TPI on cell viability has rarely been presented, this result was expected as the disruption of thymidine catabolism is more likely to result in an initial cytostatic response rather than acute cytotoxicity. Other analogous TP inhibitors have also displayed no effect on the cell viability of U87 cells . A concerning observation was that the nitroimidazolyl prodrugs 4 and 5 had more of an effect on cell viability than their corresponding active TP inhibitors in HAs (Figure S4B,C).…”
Section: Resultsmentioning
confidence: 96%
“…HsTP has been shown to degrade the anti-viral drug trifluorothymidine (TFT) as well as other fluoropyrimidines and chemotherapeutic agents (Patterson et al, 1995). These observations prompted the in-depth study of HsTP's kinetic properties and the elucidation of its catalytic mechanism (Schwartz et al, 2010;Birck and Schramm, 2004;Oh and el Kouni, 2018) to aid the development of potent inhibitors (de Moura Sperotto et al, 2019;Pérez-Pérez et al, 2005). Indeed, the inhibitor 5-chloro-6-[1-(2-iminopyrrolidinyl) methyl] uracil hydrochloride (TPI) is one of the most potent HsTP inhibitors (Ki ∼ 20 nM), capable of inducing considerable reduction in tumor growth in mice (Matsushita et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…44) Recently, Pablo Machado et al reported some novel pyrimidine acyclic azanucleosides (compounds 20-27 in Figure 4B) as human thymidine phosphorylase inhibitors. 45) The structures of these hTP inhibitors were designed and inspired by an enzyme-catalyzed transition state (Figure 4A). The introduction of halogen substituent polarized the heterocyclic ring moiety and stabilized the negative charge on the base part.…”
Section: Chemical and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%